An Addition to the Thar Desert Termites (Insecta: Isoptera) - Kumar, Sachin (Indian Forester, 2011)
The Thar Desert consists of four states in north-western India and two states in southeastern Pakistan. Six species including (Anacanthotermes macrocephalus (Desneux), Psammotermes rajasthanicus Roonwal and Bose, Coptotermes heimi (Wasmann), Heterotermes indicola (Wasmann), Microcerotermes beesoni Snyder and Odontotermes feae (Wasmann)) are recorded for the first time from the Thar Desert portion of Haryana which are addition to the 51 species of termites which are already known from this region.